Atomic and Magnetic Ordering in bcc Cu-Al-Mn: Computational Study - Alés, Alejandro (2014)
The β phase of the ternary alloy Cu-Al-Mn, with bcc structure, displays an interesting variety of long-range atomic ordering and magnetic transitions. In this work, we present a model that allows an accurate reproduction of the measured critical temperatures for alloys with compositions along the pseudobinary line Cu3Al-Cu2AlMn. The method is based on the Monte Carlo technique, allowing simultaneous evolution of the atomic distribution and the magnetic state. The configurational part of the energy is represented with a three-state Hamiltonian; the six interchange energies that govern the chemical interactions between nearest and next-nearest neighbours atoms have been determined. The magnetic counterpart is modelled by means of an Ising model. The predicted Curie temperatures agree well with the experimental values when it is assumed that the crystal configuration remains fixed and with the maximum possible degree of atomic ordering. The effects of configurational disorder on the magnetic transition have been evaluated.